Pengembangan Pariwisata Alternatif Melalui Pemanfaatan Potensi Budaya di Kabupaten Buleleng (Jurnal Ilmiah Pariwisata, 2015)
This paper aims to describe a form of an alternative tourism based on the needs and social capital culture owned by the community. Observation techniques and in-depth interviews conducted to determine the needs and capital owned by local people whose lands are developed as a regional tourism. The findings were analyzed using qualitative descriptive analysis method, which is then presented as a narrative. The findings in the field, it is understood that the social capital of culture is very much contained in Buleleng Regency society which can certainly sinergized with tourism development. Social and cultural capital is owned by the people of Buleleng can be seen from a wide variety of both sacred art form and can be used as a form of entertainment, especially the unique temple multicultural atmosphere, historical relics including literary works of the kingdom of Buleleng and beautiful nature, especially the underwater world. The amount of social capital and the culture of Buleleng, including the community, but in the context of regional tourism is not developed optimally. Therefore in this study, with the understanding of human resources, social resources, and cultural resources possessed by the people in the district of Buleleng, required a special education that is based on the needs of society as well as the understanding of the capital-owned capital that positive impact can be felt more many by all parties, especially the people than the negative effects that occur in other tourist areas in Bali. In this case, the government is also obliged to accommodate the interests and needs of local communities in order to synergy between the needs of the community with programs implemented so that the common goal of improving the quality of tourism and social welfare can be achieved.